"Agroclimatic similarity" variable developed to improve the measurement of the spatial spillover potential of agricultural R&D investments - CGIAR Research Program on Policies, Institutions, and Markets (2020)
In 2019-2020, this methodology was further applied in Ghana and Nepal and improved to capture multidimensional "agroclimatic similarity".